RMI1 Attenuates Tumor Development and is Essential for Early Embryonic Survival - Chen, Haoyi (2010)
RMI1/BLAP75 (RecQ-Mediated Genome Instability 1/Bloom Associated protein 75) is an OB-fold protein highly conserved from yeast to human. Previous studies showed that RMI1 is required for the stability of the BLM/RMI1/TopIIIα complex and for the suppression of elevated sister chromatids exchange (SCE). The presence of RMI1 strongly stimulates the Holliday dissolution activity of the Bloom helicase in vitro. The in vivo function of RMI1, however, remains largely undefined. To address this question, we generated RMI1 knockout mice through homologous replacement targeting. We found that, while RMI1(+/−) mice showed no obvious developmental phenotype, deletion of both mRMI1 alleles resulted in early embryonic lethality before implantation. To determine whether RMI1 plays a role in tumorigenesis, we generated RMI1/p53 double heterozygous mice and analyzed their onset of ionizing radiation-induced tumor development. RMI1(+/−)/p53(+/−) mice succumbed to tumor with a higher frequency and exhibited a substantially shortened survival when compared to the wild type, RMI1(+/−) and p53(+/−) cohorts. These results demonstrated a dual-role of RMI1 in embryonic development and tumor suppression.